A Method for Counting Moving People in Video Surveillance Videos. (7th June 2010) - Conte Conte, Donatello Donatello; Foggia Foggia, Pasquale Pasquale; Percannella Percannella, Gennaro Gennaro; Tufano Tufano, Francesco Francesco; Vento Vento, Mario Mario
Abstract : People counting is an important problem in video surveillance applications. This problem has been faced either by trying to detect people in the scene and then counting them or by establishing a mapping between some scene feature and the number of people (avoiding the complex detection problem). This paper presents a novel method, following this second approach, that is based on the use of SURF features and of an ϵ -SVR regressor provide an estimate of this count. The algorithm takes specifically into account problems due to partial occlusions and to perspective. In the experimental evaluation, the proposed method has been compared with the algorithm by Albiol et al., winner of the PETS 2009 contest on people counting, using the same PETS 2009 database. The provided results confirm that the proposed method yields an improved accuracy, while retaining the robustness of Albiol's algorithm.